Fintech Category Moderation Analysis: 3P Factors and Diversification in Startup Investment Decisions - Nugrhanto, Kaningar Odie; Widianingsih, Luky Patricia; Santoso, Wiliam (Jurnal Locus Penelitian dan Pengabdian, 2025)
Investment decisions are a crucial aspect of the business world, especially for startups that operate under high levels of uncertainty. This study aims to analyze the influence of people (management team), performance (startup performance), potential upside (growth potential), and diversification (portfolio diversification) on investment decisions, considering the moderating role of the startup category (fintech vs. non-fintech). The research employs a Structural Equation Modeling (SEM) approach using SmartPLS to analyze the relationships between these variables based on data collected through a survey of startup investors. The findings indicate that people and performance significantly influence investment decisions, particularly in fintech startups, which require competent management to navigate strict regulations. Potential upside is more attractive to investors in fintech startups due to the exponential growth achievable through technology, whereas diversification has a greater impact on non-fintech startups in mitigating business risks. Furthermore, the startup category serves as a moderating variable, where the effects of these four factors on investment decisions differ between fintech and non-fintech startups. The implications of this study provide insights for investors in evaluating startups before making investment decisions and assist startup founders in enhancing their business appeal. This study also contributes to the academic literature on key factors in startup investment decisions, particularly by considering the differences between fintech and non-fintech startups.